ASME 2010 10th Biennial Conference on Engineering Systems Design and Analysis, Volume 3 2010
DOI: 10.1115/esda2010-25043
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Gasoline Fumigation in a Turbocharged IDI Diesel Engine

Abstract: In the present study the effects of gasoline fumigation (GF) in a turbocharged indirect injection (IDI) diesel engine have been investigated experimentally. Here an elementary carburetor which main jet opening (MJO) can be adjusted by a fine threaded screw has been installed on the inlet pipe of diesel engine. Thus gasoline at low amounts can be injected in the inlet air ant it evaporates during intake and compression processes. The engine operates at diesel principles and it is thought that instantaneous burn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Other researchers on ethanol and ethanol fumigation have reported 30 and 50% reductions in smoke emissions, respectively . Sahin et al indicated that 10% gasoline fumigation decrease smoke opacity for about 33% at 3500 rpm.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Other researchers on ethanol and ethanol fumigation have reported 30 and 50% reductions in smoke emissions, respectively . Sahin et al indicated that 10% gasoline fumigation decrease smoke opacity for about 33% at 3500 rpm.…”
Section: Resultsmentioning
confidence: 98%
“…Zhang et al [28] indicated the combined use of fumigation methanol and diesel oxidation catalyst leads to a reduction of HC, CO, NO x , particulate mass and particulate number concentrations at medium to high engine loads. Sahin et al [25,29] recommended that gasoline fumigation can be effectively employed in existing diesel engine to improve engine performance and to reduce NO emission. Sahin et al [30] investigated theoretically the effects of light fuel fumigation, such as ethanol and gasoline, on a DI diesel engine performance characteristics and exhaust emissions.…”
Section: Introductionmentioning
confidence: 99%
“…In cold region, diesel engine starting is a major problem 7 and utilization of kerosene with diesel is a good option in order to overcome such problem as it has superior cold flow characteristics. 7 Adulterated diesel fuel is mainly used in off-road applications in which IDI engines are widely employed [26][27][28][29] and a meagre number of research works have been done on adulteration. Moreover, prediction by ANN model on the performance and exhaust emission characteristics of an IDI engine associated with the adulteration of diesel fuel with kerosene along with fuzzy-based optimization in IDI engine is uncharted.…”
Section: Motivation Of the Workmentioning
confidence: 99%
“… where,. MOS = maximum observed value during sampling for the measured pollutant. MIS = minimum observed value during sampling for the measured pollutant. ASU = uncertainty of measurement of the respective pollutant by the analyser. 28–32 …”
Section: Experimental Set-up and Proceduresmentioning
confidence: 99%
“…Thus, EF experiments were performed on turbocharged version of this engine. The EF results for turbocharged engine version were presented in references (Sahin et al 2010, Sahin et al 2015.…”
Section: Experimental System and Procedures Engine And Experimental Set Upmentioning
confidence: 99%